Association of whole blood lead level with advanced colorectal neoplasia: a population-based case-control study - Lihe PENG; Xue ZHANG; Yuanliang HE; Jiayu LI; Jiawei LI; Kun CHEN; Aiping XIE; Mingjuan JIN (Editorial Office of Chinese Journal of Public Health, 2023)
Objective To explore the association between whole blood lead concentration and advanced colorectal neoplasia (CRN) and to provide evidence for colorectal cancer (CRC) prevention and control. Methods The cases of the study were 272 advanced CRN identified from April 2014 to December 2016 in the participants of a CRC early diagnosis and treatment program including face-to-face questionnaire interview, physical examination and laboratory test conducted among the residents of Jiashan county, Zhejiang province; the 605 controls were gender- and age (± 5 years)-frequency matched healthy participants of the program. Results The geometric mean (geometric standard error) of whole blood lead concentration (μg/L) were 28.11(1.64) and 26.87 (0.93) for the cases and controls, without statistically significant difference (P > 0.05). After adjusting for gender, age, education, smoking, alcohol consumption, physical exercise, family history of CRC and body mass index (BMI), unconditional multivariate logistic regression analysis demonstrated that the participants with the highest quintile (Q5) of whole blood lead concentration were at an increased risk of advanced CRN (odds ratio [OR] = 1.87, 95% confidence interval [95%CI] : 1.15 - 3.04) compared to those with the lowest quintile (Q1) and the increased risk was much higher for the male participants (Q5 vs. Q1: OR = 2.12, 95%CI : 1.05 - 4.30). Furthermore after base 10 logarithm conversion, each unit increment in blood lead concentration was associated with a 1.86 (OR = 2.86, 95%CI : 1.28 - 6.35) and 3.98 (OR = 4.98, 95%CI : 1.62 - 15.35) times higher risk of advanced CRN for the all and the male participants, respectively. Restricted cubic spline analysis revealed a significant linear correlation between the increment of whole blood concentration and the increased risk of advanced CRN after adjusting for potential confounders mentioned above (χ2 total = 8.79, Ptotal = 0.012; χ2 non-linearity = 2.17, Pnon-linearity = 0.141). ConclusionBlood lead concentration may be associated with an increased risk of advanced colorectal neoplasia, suggesting a potential role of lead exposure in the etiology of colorectal carcinogenesis.